2019
DOI: 10.3390/ijerph16204045
|View full text |Cite
|
Sign up to set email alerts
|

Parenting Practices, Life Satisfaction, and the Role of Self-Esteem in Adolescents

Abstract: Introduction: Studies have shown significant associations between parenting practices, life satisfaction, and self-esteem, and the role of parenting practices in adolescent adjustment, emphasizing its influence on wellbeing. Objectives: To analyze the relationships between parenting practices, self-esteem, and life satisfaction, and test the mediating effect of self-esteem on the relationship between the different parenting practices and life satisfaction of adolescents. Method: The sample came to a total of 7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
43
0
11

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(57 citation statements)
references
References 46 publications
3
43
0
11
Order By: Relevance
“…The range of total scores on the sections of the four-item authoritarian parenting, five-item authoritative parenting, and four-item indulgent parenting was 4–20, 5–25 and 4–20, respectively. We had developed the questionnaire items regarding the parent’s knowledge about the development of self-esteem in adolescents based on the following literatures: [ 1 , 2 , 3 , 4 , 7 , 11 , 30 , 31 , 68 ]; we had developed the items on parenting practice related to self-esteem based on the following literatures: [ 7 , 11 , 33 , 36 , 56 , 68 , 69 , 70 , 71 , 72 , 73 ]; and we had developed the items on parenting style based on the following literatures: [ 39 , 40 , 42 , 43 , 44 , 45 , 47 , 48 , 49 , 50 , 56 , 60 , 74 , 75 , 76 ]. The tool was developed in Nepali.…”
Section: Methodsmentioning
confidence: 99%
“…The range of total scores on the sections of the four-item authoritarian parenting, five-item authoritative parenting, and four-item indulgent parenting was 4–20, 5–25 and 4–20, respectively. We had developed the questionnaire items regarding the parent’s knowledge about the development of self-esteem in adolescents based on the following literatures: [ 1 , 2 , 3 , 4 , 7 , 11 , 30 , 31 , 68 ]; we had developed the items on parenting practice related to self-esteem based on the following literatures: [ 7 , 11 , 33 , 36 , 56 , 68 , 69 , 70 , 71 , 72 , 73 ]; and we had developed the items on parenting style based on the following literatures: [ 39 , 40 , 42 , 43 , 44 , 45 , 47 , 48 , 49 , 50 , 56 , 60 , 74 , 75 , 76 ]. The tool was developed in Nepali.…”
Section: Methodsmentioning
confidence: 99%
“…The research of the mechanism of parenting style on college student's emotional distress is essential to better understand the theory in this field and to develop effective interventions to prevent or decrease emotional distress for college students. According to the ecological system model, parenting style is a crucial family factor affecting the personality development of the offspring (Heaven and Ciarrochi, 2008;Pérez-Fuentes et al, 2019). For example, Heaven and Ciarrochi (2008) conducted a longitudinal study and found that the authoritative parenting style that students perceived in seventh grade predicted an increase in student's conscientiousness in eighth grade.…”
Section: The Mediating Role Of Zhongyong Thinkingmentioning
confidence: 99%
“…Acquiring great importance are the roles of personal variables, especially self-esteem, in the father-son interaction and in the improvement of the subjective well-being of the adolescent [27]. However, the parents' educational styles continue to be of great importance in favoring that adolescents feel satisfied with life and have positive self-esteem [11,[28][29][30][31][32], so the family has a decisive role in prevention and protection of children from risk behaviors [32,33], although sometimes discrepancies appear between the expectations of parents and their children [27].…”
Section: Introductionmentioning
confidence: 99%